25(OH)D Concentration in Neonates, Infants, and Toddlers From Poland—Evaluation of Trends During Years 1981–2011 - Wójcik, Marek; Jaworski, Maciej; Pludowski, Pawel (Frontiers in Endocrinology, 2018)
Abstract Introduction: The numerous evidence showing spectrum of vitamin D effects on human health resulted in an update of vitamin D supplementation guidelines, and raised discussion on the risk of hypercalcaemia as a result of announcing novel recommendations. The aim of this study was to analyse the trend in serum 25-hydroxyvitamin D concentration (25(OH)D) change over the 30 years of activity of a single paediatric diagnostic unit. Materials and methods: Calcium-phosphate metabolism markers and 25(OH)D concentrations were analysed in a group that consisted of newborns and infants commissioned for diagnostics due to suspected calcium-phosphate metabolic disturbances (n = 3163; mean age 9.0 ± 3.0 months). Results: In neonates and infants 25(OH)D <10 ng/ml was noted in 4.5% of patients (n = 163), 10-20 ng/ml in 14.7% (n=465), 20-30 ng/ml in 23,9% (n=756) and 30-50 ng/ml in 35.9% (n=1136). The mean 25(OH)D concentration in analysed group as whole was 37.5 ± 24.5 ng/ml. In patients with 25(OH)D concentration <10 ng/ml normal calcaemia (2.25-2.65 mmol/l) was noted in 83.4% of neonates and infants (n = 136). 81 subjects had 25(OH)D concentrations above 100 ng/ml, with co-existing calcaemia range: 2.6 mmol/l up to 4.38 mmol/l (mean Ca = 2.69 mmol/l). Hypocalcaemia (Ca < 2.25 mmol/l) was observed in 0.54%, (n = 17). 13.8% patients revealed calcium levels > 2.65 mmol/l (n=435). In general, the average values of calcium-phosphate markers were within the reference range values according to age. The highest mean 25(OH)D concentration of 51.8 ng/ml ± 38.8 was noted in years 1981-1999 (n = 305). The lowest average 25(OH)D value was observed in years 2010-2011 (29.0 ng/ml ± 13.6; n = 412). The trend of decreasing 25(OH)D concentration during analysed time period was significant (r=-0.29, p<0.0001). Conclusions: 80 % of children aged 0-36 months had 25(OH)D concentration > 20 ng/ml, however, during 3 decades an average 25(OH)D concentrations trended significantly to decrease. A direct relationship between low 25(OH)D concentration and hypocalcaemia was not observed nor between high 25(OH)D concentration and hypercalcemia.